Influence of Roughness on the Asymmetric Flow Field of a Slender Body - Kai Wei; Shaosong Chen; Yihang Xu; Dongdong Tang (International Journal of Aerospace Engineering)
Low speed and high angle of attack are problems that must be faced in vertical launching missiles. A natural asymmetric vortex phenomenon occurs at a low speed and high angle of attack of a slender body. In this paper, the Detached Eddy Simulation (DES) method is adopted to simulate the asymmetric flow of a slender body at a high angle of attack. The influence of roughness is analysed from the flow field and pressure distribution. And the DES method is verified by comparing it with the wind tunnel test results. The flow fields of the four models with the surface roughness of 0, 0.8, 5, and 100 are compared. The downstream flow still appears asymmetric when the surface is smooth, indicating that the stability of the flow field is not enough to maintain the symmetry of the flow field. The simulation results show that the adverse pressure gradient increases in the region where the boundary layer separates with the roughness greatly increasing, but the structure of the flow field at the head is slightly different. On the whole, the surface pressure and lateral force per unit length (Cfzpm) transform alternately along the axial direction, and the period of alternating reverses increases with the increase of roughness. Finally, the pressure tends to be in equilibrium, and Cfzpm approaches zero. It should be noted that the distribution of Cfzpm is slightly different on the head, indicating that the asymmetry of pressure on the cylinder section is an important factor controlling the magnitude and the direction of lateral force. The influence of roughness on the flow around a slender body is acquired in this paper, and it has reference significance to the roughness problem of the actual missile.